Capitalism, Wealth, and the Question of (In)Visibility The Thyssen Family and Its Investments - Derix, Simone (Reshaping Capitalism in Weimar and Nazi Germany, 2022)
In the 1920s and early 1930s, both the public and scholarly understanding of capitalism was governed by a logic of individual visibility. This angle, however, can easily obscure the fact that invisibility helped shape German society as a capitalist society too. The chapter thus argues that a focus on the interplay of visibility and invisibility can improve our understanding of capitalism in Germany and beyond. By way of example, it analyzes the investment practices of the ultra-wealthy industrialist Thyssen family. It elucidates their opportunities of keeping capital invisible by concentrating public attention to specific family members within the bounds of a nation or Europa, thereby enabling hidden networks of less prominent family members and asset managers to act globally. Although these practices emerged within the specific historical context of the interwar period, they remain relevant today. The chapter thus highlights the long-standing history of exploiting invisibility in capitalist societies.<br
CRIS-Team WoS Importer:2022-12-30
Keywords: asset management; capitalism; economic inequality; social inequality; tax avoidance; transnational history; visibility; wealth